Gambaran Manajemen Keselamatan Pasien di RSGM Unimus Berdasarkan Agency For Health Research And Quality Care (AHRQ) - Dwi Windu Kinanti; Retno Kusniati (Jurnal Manajemen dan Administrasi Rumah Sakit Indonesia (MARSI), 2020)
ABSTRACTBackground: RSGM Unimus is a dental and oral hospital that has been operating since 2019. Building a culture of patient safety in the hospital is the responsibility of all staff in the hospital to patients. Patient safety is a system by which the hospital makes patient care safer. Efforts to minimize the occurrence of patient safety incidents, hospital management needs to build a patient safety culture to improve the quality and service of patients in the hospital. Hospital patient safety can be measured using the Hospital Survey on Patient Safety Culture issued by AHRQ (Agency for Health Research and Quality Care). In this case, patient safety culture is measured from the perspective of medical personnel and staff in the hospital. Objective: Describe patient safety at RSGM Unimus based on AHRQ according to dentists, young dentists and medical staff. Method: This type of descriptive quantitative research with a cross sectional research design, determining the sample using the Proportionate Startified Random Sampling technique using the Slovin formula obtained 65 respondents. Result: 6 Dimensions of patient safety according to AHRQ get a positive response including: Dimension 1 Internal cooperation (88.2%), Dimension 2 Manager / supervisor (90.76%), Dimension 3 communication (90%), Dimension 4 reports of errors in action (82.56%), Dimension 5 patient safety rate (92.30%), Dimension 6 overall hospital management (87.41%). The majority of positive responses (> 75%) in human resources at RSGM Unimus support patient safety culture. Conclusion: The culture of patient safety at RSGM Unimus can be said to be very good, meaning that RSGM Unimus supports the culture of patient safety and has carried out patient safety very well.Keywords: Patient Safety, AHRQ (Agency for Health Research and Quality Care)